TERJEMAH DALAM SEJARAH KEILMUAN ISLAM ABAD PERTENGAHAN - Laila, St. Noer Farida (Pusat Pengembangan Bahasa IAIN Tulungagung, 2012)
It is a fact that medieval Moslem scholars did really contribute to the development and preservation of human knowledge. A great deal of Greek and Persian knowledge is preserved through a creative process known as translation. Historically, the translation of the most important texts form Greek and Persia into Arabic was carried out within the Abbasid court. Great libraries and schools thrived on the works that the translators contributed. However, translation of Greek books into Arabic had begun earlier under the Umayyad times late in the seventh century. During the Umayyad, translation became one of the prominent causes behind strengthening the new Islamic state. It was also the main reason that Arabic became the lingua franca for many centuries.